Jurimetrics Implementation of Determining Wife's Rights in Divorce in Talu Religious Court - Fadhilah, Defi Rahmi; Salma, Salma; Elfia, Elfia; Mawaddah, Arini Alfa (Jurnal Ilmiah Al-Syir'ah, 2023)
This study delves into post-divorce wives' rights, particularly examining the impact of Jurimetrics. Divorce rulings often inadequately support these rights. The Talu Religious Court, part of the Padang High Religious Court, employs Jurimetrics due to disputes over divorce-related issues. Through normative legal research and content analysis, it's evident that Jurimetrics-influenced decisions notably enhance wives' rights compared to non-Jurimetrics rulings. These decisions prioritize fairness by considering factors like minimum wage, husband's income, and marriage duration. Notably, the application of Jurimetrics in divorce proceedings consistently leads to more equitable and just outcomes for wives, presenting a systematic and fair approach rooted in principles of fairness and justice. Overall, employing Jurimetrics significantly bolsters the protection of post-divorce wives' rights, providing a methodological framework founded on fairness and equity within divorce adjudications.